Estrategias didácticas de lectura para mejorar la comprensión lectora en estudiantes de EGB Superior de la U.E. Melvin Jones del cantón El Empalme. 2022 - Bravo Bravo, Andrea Elizabeth (2022)
In the present research work the topic was addressed: Didactic reading strategies to improve reading comprehension in students of Superior Basic General Education (8th, 9th and 10th grades) of the Melvin Jones Educational Unit of the El Empalme canton, it is proposed to contribute to the improvement of the teaching-learning process of the students through the design of reading sheets that include interactive and dynamic exercises focused on the animation of reading and text comprehension. As a General objective, it was established to propose didactic reading strategies to improve reading comprehension, where, with the diagnosis of the characteristics and the identification of the influential factors in the reading comprehension of the students of this educational level, it allowed the application of strategies of reading, the same ones that through the opinion of experts determined the influence generated in the comprehension of the text of the students. A mixed approach methodology with a non-experimental design was selected. The theoretical bases that provide the support and scientific value to this research are given through the collection of information obtained from digital texts, scientific articles, international news, among others. The results obtained show that the use of didactic reading strategies improve the reading comprehension of higher EGB students, and therefore, their academic performance, contributes significantly to the work of teachers, since when applying the reading sheets in the Your class plans will have in your favor a didactic resource to strengthen, improve and innovate your educational practice allowing your students to acquire and develop linguistic and communication skills.